'A magnificent business prospect . . .' the Coase theorem, the extortion problem, and the creation of Coase theorem worlds. Issue 2 (24th June 2014) - MEDEMA, STEVEN G.
Abstract: The Coase theorem, circa the 1970s, had no settled meaning or content; instead, that meaning and content was created – and in differing ways – by the modeling choices of scholars who attempted to grapple with and assess the proposition that Coase had laid out in 1960. These modeling decisions included both the theoretical frameworks laid onto the theorem and the assumptions (including meanings ascribed thereto) said to underlie it. The present article illustrates this using the 1960s and 1970s extortion debate as a backdrop, showing how conclusions reached regarding the theorem's validity hinged on the Coase theorem worlds created by the authors involved.